Profit distribution management and Islamic banks market power - Risfandy, Tastaftiyan (Universitas Sebelas Maret, 2019)
Operating in the competitive dual banking market, Islamic banks’ behavior often mimics conventional banks. One of the ways to do this is by managing their earnings so that their deposit rate of return could be closely pegged to the conventional banks’ deposit interest rate. Farook et al. (2012) define this term as “profit distribution management” or PDM. This paper investigates whether PDM practice in Islamic banks is affected by their market power. Using a sample of Islamic banks from 2009 to 2013 from Indonesia, the most populous Muslim country adopting dual banking market, we find that bank with a high market power are less engage in PDM. This means that, when Islamic banks are able to set high price of their banking product in the competitive market, they are already reach specific market position. In this case, Islamic banks is observed manage their earnings but in the lower intensity. We also provide empirical evidence that other factors such as governance structure and market share of Islamic banks are also matter for the PDM. Some policy implications are discussed.